A record of bottom water temperature and seawater δ18O for the Southern Ocean over the past 440 kyr based on Mg/Ca of benthic foraminiferal Uvigerina spp - Elderfield, H.; Greaves, M.; Barker, S.; Hall, I. R.; Tripati, A.; Ferretti, P.; Crowhurst, S.; Booth, L.; Daunt C. (Quaternary Science Reviews, 2010)
The sensitivity to temperature of Mg/Ca ratios in the shallow-infaunal benthic foraminifera Uvigerina spp. has been assessed. Core-top calibrations over similar to 1-20 degrees C show a range in sensitivity of 0.065-0.084 mmol/mol/degrees C but few data are available spanning the temperature range anticipated in deep-sea records over glacial-interglacial cycles. In contrast to epibenthic foraminiferal species, carbonate ion saturation appears not to affect Mg/Ca significantly. A method based on estimating the ratio of the temperature sensitivity of foraminiferal Mg/Ca to that Of delta O-18(calcite) shows that sensitivity for Mg/Ca at the high end of the observed core-top range (similar to 0.1 mmol/mol/degrees C) is required for consistency with LGM-Holocene differences in each property as constrained by independent proxy data. This is supported by a Mg/Ca record for Uvigerina spp. generated for the Southern Ocean over the past 440,000 years from Ocean Drilling Program Site 1123 (Chatham Rise, New Zealand). The record shows variability that correlates with climate oscillations. The LGM deep ocean temperature derived from the Mg/Ca record is -1.1 +/- 0.3 degrees C. Transformation to temperature allows estimates to be made of changes in bottom water temperature and seawater delta O-18 and comparison made with literature records. Analysis reveals a similar to 2.5-kyr lead in the record of temperature over calcite delta O-18 and a longer lead over seawater delta O-18. This is a reflection of larger phase offsets at eccentricity periods; phase offsets at tilt and precession are within error zero.